2017
DOI: 10.2337/db16-0755
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide 1 and Its Analogs Act in the Dorsal Raphe and Modulate Central Serotonin to Reduce Appetite and Body Weight

Abstract: Glucagon-like peptide 1 (GLP-1) and serotonin play critical roles in energy balance regulation. Both systems are exploited clinically as antiobesity strategies. Surprisingly, whether they interact in order to regulate energy balance is poorly understood. Here we investigated mechanisms by which GLP-1 and serotonin interact at the level of the central nervous system. Serotonin depletion impaired the ability of exendin-4, a clinically used GLP-1 analog, to reduce body weight in rats, suggesting that serotonin is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 53 publications
1
63
1
4
Order By: Relevance
“…Anderberg et al [32] demonstrated that long-term stimulation with GLP-1RAs promoted an increase in the expression of serotonergic receptors in the hypothalamus. In addition, they showed that the 5-hydroxytryptamine 2A (5-HT 2A ) receptor is crucial for GLP-1RA-induced weight loss after exendin-4 ICV injection, such as peripheral injection of liraglutide in rats.…”
Section: Glp-1 Receptor Agonists (Glp-1ras) In the Central Nervous Symentioning
confidence: 99%
“…Anderberg et al [32] demonstrated that long-term stimulation with GLP-1RAs promoted an increase in the expression of serotonergic receptors in the hypothalamus. In addition, they showed that the 5-hydroxytryptamine 2A (5-HT 2A ) receptor is crucial for GLP-1RA-induced weight loss after exendin-4 ICV injection, such as peripheral injection of liraglutide in rats.…”
Section: Glp-1 Receptor Agonists (Glp-1ras) In the Central Nervous Symentioning
confidence: 99%
“…Supporting the notion that the brain plays a seminal role in glycemic control, coadministration of Lorcaserin with metformin or sulfonylureas potentiates the ability of the antidiabetic agents to improve HbA1c and fasting glucose levels in obese subjects with T2D (Moore, 1990). Preclinical studies have explored the prospect of combinatorial targeting of 5-HT2A/C receptors and GLP-1RAs (Anderberg et al, 2017), and it appears that the benefits of Lorcaserin can be increased in combinatorial settings.…”
Section: H Lorcaserinmentioning
confidence: 98%
“…An important orexigenic signal leading to hunger and food intake is ghrelin which is produced in the stomach [77]. Anorexigenic signals from the body periphery include glucose, the enterocyte hormone glucagon-like peptide-1 (GLP-1) [78], the pancreatic hormone insulin and the fatty tissue hormone leptin [76]. In the hypothalamus, the arcuate nucleus, the paraventricular nucleus and the lateral hypothalamus are of particular relevance for weight regulation [76,79].…”
Section: Neural Circuits and Neurotransmittersmentioning
confidence: 99%